IMPORTANCE OF THE BEEKEEPING SECTOR IN REGIONAL AGRICULTURE (American Journal of Business Management, Economics and Banking, 2024)
In the world, 80-85% of plants are pollinated from the outside, and bees play a key role in this. Beekeeping is a rapidly developing branch of Agriculture, and it is noteworthy that it itself is at the same time divided into a number of independent scientific departments. Currently, large-scale work is being carried out to develop the beekeeping sector with the initiatives of our honored President.